Extracting Protein from Antarctic Krill (Euphausia superba). Issue 4 (18th May 2016) - Qi, Xiang-Ming; Liao, E.; Wang, Lu; Lin, Hong; Xue, Chang-Hu
ABSTRACT: The isoelectric solubilization/precipitation (ISP) process was applied to Antarctic krill protein extraction. The solubility of Antarctic krill proteins and their fluoride content were studied between pH 1.00–13.75. The previous krill protein extraction conditions using ISP were improved. Excess fluoride in Antarctic krill was removed using a water-washing method according to its solubility. To save water, a multistage countercurrent system was used to optimize the ISP method. The results showed that the solubility of Antarctic krill proteins reached a minimum at pH 4.5 and a maximum at pH 13.5, while the concentration of dissolved fluoride was relatively unchanged (16.78–20.50 mg/L), with pH 2.00–13.50. Water-washing 4 times could reduce fluoride 98.14 ± 0.01% from krill with about a 5.14 ± 0.21% protein loss. The reduction allows krill protein to meet the Chinese National Standard (GB 2762-2005) for fluoride. Meanwhile, the four-stage countercurrent system achieved almost the same high fluoride removal rate (98.58 ± 0.01%) using only 25% of the water.